Persisting fetal clonotypes influence the structure and overlap of adult human T cell receptor repertoires - Pogorelyy, Mikhail V.; Elhanati, Yuval; Marcou, Quentin; Sycheva, Anastasiia L.; Komech, Ekaterina A.; Nazarov, Vadim I.; Britanova, Olga V.; Chudakov, Dmitriy M.; Mamedov, Ilgar Z.; Lebedev, Yury B.; Mora, Thierry; Walczak, Aleksandra M. (PLoS computational biology, 2017)
The diversity of T-cell receptors recognizing foreign pathogens is generated through a highly stochastic recombination process, making the independent production of the same sequence rare. Yet unrelated individuals do share receptors, which together constitute a "public" repertoire of abundant clonotypes. The TCR repertoire is initially formed prenatally, when the enzyme inserting random nucleotides is downregulated, producing a limited diversity subset. By statistically analyzing deep sequencing T-cell repertoire data from twins, unrelated individuals of various ages, and cord blood, we show that T-cell clones generated before birth persist and maintain high abundances in adult organisms for decades, slowly decaying with age. Our results suggest that large, low-diversity public clones are created during pre-natal life, and survive over long periods, providing the basis of the public repertoire.